AGRICULTURE OF THE CZECH REPUBLIC IN THE 21ST CENTURY: FROM PRODUCTIVISM TO POST-PRODUCTIVISM - Věžník, Antonín; Král, Michael; Svobodová, Hana (Quaestiones Geographicae, 2013)
During last two decades Czech agriculture has gone through significant changes: the transition of agriculture in the 1990s and the entrance of the Czech Republic into the EU and its commitment to the Common Agricultural Policy (CAP). Both of these changes contributed to the structural and regional differentiation of Czech agriculture and exposed it to competition with the whole of Europe. Furthermore, CAP exposed Czech agriculture to uneven conditions for farmers within the EU. The most significant results of these changes have been a decrease in the agricultural sector output, a reduction in farm animals bred, and shrinkage of arable land. On the other hand, many non-productive and non-agricultural activities in the rural areas are subsidised, which offers farmers new possibilities of development. The aim of this paper is to analyse the structural and spatial change in Czech agriculture between 2000 and 2010 on the basis of Agrocenzus data supplemented by opinions of farmers gained in a series of interviews.